Knowledge as Factor Increase Frequency of Vaginal Discharge in District Demak - Rita Kartikasari; Yulice Soraya Nur; Nugroho Susanto (Public Health Faculty, Hasanuddin University, 2020)
ABSTRACTIncidence of abnormal vaginal discharge is high in developing countries. Abnormal vaginal discharge is symptom of reproductive tract infections and sexual transmitted diseases. Knowledge vaginal discharge important for prepare and preventive abnormal vaginal discharge and improving practice hygiene sanitary. The study propose correlation knowledge of vaginal discharge with frequency of vaginal discharge. Study design was cross-sectional, sample were collected 60 participant. Data were collecting with interview by questioner. Data were analysis SPSS under 0.05 regarded as statistically significant with pearson correlation. Mean score of indicators definition 73,05±17,11, caused 81,11±12,82, prevention 63,83±16,06, impact 60,74±16,92, and total knowledge 60,74±16,92. Indicator of definition no significant correlation with vaginal discharge p = 0,072, indicators of caused significant correlation with vaginal discharge p = 0,002, indicators of preventive no significant correlation with vaginal discharge p = 0,067, indicators of impact significant correlation with vaginal discharge p = 0,032. Total knowledge significant correlation with vaginal discharge p = 0,005. Knowledge of vaginal discharge average high, indicators dominant is caused compare other indicators. Knowledge was significant correlation with vaginal discharge.Keywords : vaginal discharge, knowledge, adolescent.